Monetary economics in developing countries - Ghatak, Subrata (New York : St. Martin's Press, 1981)
This book is intended as an up-to-date undergraduate text for students taking a course on monetary economics in less-developed countries (LDCs). Also important issues confronting the LDCs in the use of monetary and theory policy have been discussed carefully and rigorously.
Includes bibliographies and index.
usc 31/05/17
Loans
Keywords: Money; Monetary policy; Developing countries